Testing of a novel Valsalva Assist Device with supine and modified positions in healthy volunteers. Issue 1 (1st December 2018) - FitzGerald, Isabel; Ewings, Paul; Lang, Iain; Appelboam, Andy
Abstract : Background: The Valsalva manoeuvre (VM) is used to treat supraventricular tachycardia (SVT) by inducing a vagal response (drop in HR). There is debate as to the best position in which to carry out the VM and how the strain should be delivered in practice. We aimed to compare vagal responses induced with supine and modified VMs using strains delivered with a standardised manometer or novel Valsalva Assist Device (VAD), a simple device to provide resistance to exhalation. Methods: We conducted a repeated measures randomised trial of four VMs (two supine VM and two modified VMs), in healthy adult volunteers, with strains delivered using an adapted sphygmomanometer (manometer) or a VAD. Changes in HR, pressure and duration of strain and adverse events were monitored and compared between the techniques and devices. The trial was approved by the University of Exeter Medical School Research ethics committee. Results: 75 healthy participants aged 19–55 years were recruited over a 4-month period. A mixed-effects linear regression showed the modified VM resulted in a 3.8 beats per min (bpm) greater drop in HR compared with the supine VM (p=0.002, 95% CI 2.2 to 5.4). VM strains produced by the VAD were of a similar pressure but of slightly shorter duration and resulted in a 1.9 bpm smaller drop in HR compared with the manometer (p=0.01, 95% CI 0.4 to 3.4). There were no differences in adverse events. Conclusions: Modified VM was associated with a greater drop in HR than a supine VM with no increase in adverse events in healthy volunteers. The VAD can be used to safely generate the recommended VM strain pressure, but produced a smaller drop in HR compared with a manometer and requires modification to enable the recommended strain duration to be achieved consistently. Trial registration number: NCT03298880 .